Can Financial Assistance Mediate the Training and Human Capital Relationship for Pakistani Women Micro Entrepreneurs? - Tara, Nain; Arshed, Noman; Aziz, Osama; Yamin, Mahwish (International Journal of Economics and Financial Issues, 2020)
Women participation in the economy can help accumulate capital formation and ideation which helps them in becoming a tool for socio-economic uplift for poor people working in the informal sector of the economy. The current research has examined the impact of financial assistance programs provided to micro and small women entrepreneurs, on the economic capital formation. Assistance programs include training and financial assistance. This research also aimed to investigate the mediating role of financial assistance between training assistance and economic capital. The methodology included empirical study, collection of data from 350 women micro-entrepreneurs from Southern Punjab in Pakistan, and analysis is conducted with the help of SPSS. Findings revealed that training assistance program has a significant impact on capital formation. While the mediation test confirmed the mediation of financial assistance between the training and economic capital. Keywords: Economic Capital, Financial Assistance, Informal Economy, Vocational Training, Women Micro entrepreneurs. JEL Classifications: G21, I22, I23, L26 DOI: https://doi.org/10.32479/ijefi.9833